Fiscal-monetary policy coordination and central bank independence - Olli Castrén (Bank of Finland, 1998)
This study contains four essays in the areas of fiscal-monetary policy coordination, public finance and optimal monetary institutions. Essay 1 analyses inflation targeting in an economy with decentralised monetary and fiscal policies and centralised wage setting.Depending on the specification of the trade unions' utility functions, both fiscal and monetary policy can be subject to time-inconsistency problems.Inflation targeting can achieve society's optimal outcome in this model only when the trade unions do not have an employment target which is lower than full employment.The result is robust to uncertainty about the monetary authority's preferences. Essay 2 studies inflation targeting in the context of a monetary union.The setup resembles the Maastricht treaty where a politically representative council delegates monetary policy to an independent central bank.The optimal delegation decision is shown to include an inflation target and a central banker with conservative preferences.It is shown that fiscal discipline in the union increases under such optimal delegation.Moreover, if the voting rules for the delegating council are designed optimally, the council's incentives to renegotiate ex post the central bank's target can be eliminated. Essay 3 focuses on Central Bank (CB) institutions and fiscalmonetary policy coordination under debt stabilisation programmes.When the government and the CB cooperate, a less inflation-averse CB induces faster debt reduction.Under non-cooperative strategies, the opposite result holds.In the presence of political instability, the government shifts fiscal adjustment to the future.Additional adjustment time does not alleviate the situation, but electoral incentives can induce earlier adjustment. Essay 4 looks at optimal fiscal policy in the presence of foreseeable shocks.When the government cares about the future, the deficit is optimally set lower before the arrival of the shock and more adjustment effort is shifted from ex post to ex ante.In EMU, fiscal policy will be constrained by the Stability and Growth Pact, which penalises excessive deficits.Thus, in the presence of shocks, fiscal policy before the shock can become highly restrictive under the pact.
URN:NBN:fi:bof-201408071696
Keywords: 330; fiscal-monetary policy coordination; optimal institutions; inflation targeting; dynamic budget constraint; debt stabilisation.